Effect of The Application of The Problem Based Learning Model to The Mathematical Problem Solving Ability - Siska Ermayeni; Lucky Heriyanti Jufri; Melisa Melisa (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
This research is motivated by the low mathematics learning outcomes in terms of the results of daily mathematics tests of students of class XI MIPA SMAN 1 Sungai Limau. The results of these tests are influenced by the low ability of students to solve mathematical problems and the inability of students to solve non-routine problems. This study aims to determine whether there is an influence of the application of the Problem Based Learning (PBL) model to the mathematical problem-solving ability of students of class XI MIPA 1 of SMAN 1 Sungai Limau. Data collection techniques used are by giving a description test in the form of pre-test and post-test. Analysis of test data containing indicators of the ability to solve mathematical problems using the t-test. The calculation results obtained t-value = 5,57 with N = 30 and Î± = 0,05. While Â = 1.70, Â then reject H0. So, it can be concluded that there is an effect of the application of the Problem Based Learning (PBL) model to the mathematical problem-solving ability of students of class XI MIPA 1 of SMAN 1 Sungai Limau